Gail Gerhart interviews Robert Mangaliso Sobukwe (1970) - Gerhart, Gail (PINS-Psychology in Society, 2024)
Robert Sobukwe (1924-1978) grew up in Graaff-Reinet, attended Healdtown, and graduated in 1949 from Fort Hare where he had a distinguished academic record and showed promise as a public speaker. He became a teacher in Standerton, and later taught African languages at the University of the Witwatersrand in Johannesburg. In April 1959 he was elected president of the Pan Africanist Congress at its founding. Jailed in the aftermath of the PAC’s anti-pass campaign in March 1960, during which the Sharpeville massacre occurred, Sobukwe spent nine years in prison, six of them in solitary confinement on Robben Island. After his release in 1969, he was denied an exit permit to take up employment offered to him in the United States. He was restricted to Kimberley, banned from meeting with more than one person at a time, and from contributing to the preparation of any publication. This interview was conducted by Gail Gerhart, at that time a graduate student at Columbia University in New York City. It took place during the mornings of August 8 and 9, 1970, in a rental car on the outskirts of Kimberley. Because of police surveillance and Sobukwe’s banning order, no notes were made until after Sobukwe was no longer present, when the notes below were spoken onto a tape recorder by the interviewer. The notes are verbatim only where indicated by quotation marks, and otherwise reflect the interviewer’s best recollection of what was said. This interview has been made available on condition that proper acknowledgment is made for use of any of its contents. The original USAmerican spelling is maintained in this interview.